Rabbits Die of Cat Bites, So Why the Fuss? - Casey, Shirley (Wildlife Rehabilitation Bulletin, 2009)
It is common for small birds and mammals injured by cats to be presented to rehabilitators. Many of these injured animals die as a result of the cat bites, either because of the severe punctures and lacerations, or because of infection transmitted by bacteria from the cat’s mouth. This case highlights the importance of a rehabilitator paying close attention and acting on what may seem like an a familiar case of a rabbit dying from a cat bite, when actually a zoonotic disease caused the death. The article closes with reminders for rehabilitators such as collecting the rescuer’s contact information, using safe handling protocols, and not assuming an obvious problem described by the rescuer is the primary consideration.